2011
DOI: 10.1590/s0066-782x2011005000104
|View full text |Cite
|
Sign up to set email alerts
|

Características psicológicas dos pacientes submetidos à intervenção coronária percutânea

Abstract: Background: There is few data evaluating the prevalence and influence of adverse psychological characteristics on the prognosis of individuals submitted to percutaneous coronary interventions. No study has addressed this issue in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Yu et al [13] used the 9-Question Primary Care Evaluation of Mental Disorders Brief Patient Health Questionnaire-9 to define depression (non-depressed ≤4, depressed 5–27). Schmidt et al [14] identified patients with depression using the Beck Depression Inventory with 20 points as the cut-off value. The study by Li et al [10] defined depression according to the Zung Self-Rating Depression Scale.…”
Section: Resultsmentioning
confidence: 99%
“…Yu et al [13] used the 9-Question Primary Care Evaluation of Mental Disorders Brief Patient Health Questionnaire-9 to define depression (non-depressed ≤4, depressed 5–27). Schmidt et al [14] identified patients with depression using the Beck Depression Inventory with 20 points as the cut-off value. The study by Li et al [10] defined depression according to the Zung Self-Rating Depression Scale.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies suggest that persons who responded to their illness by perceiving control over their futures, by having positive expectations about their futures, and by holding a positive view of themselves seemed to be at less risk for a new cardiac event after a first PTCA. In some studies, it was also noted that depression and anxiety constituted independent risk factors for cardiovascular adverse events following myocardial infarction [16]. There is a paucity of Indian studies in this field.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the extended potential of communication, in Europe, cardiovascular patients experiencing coronary angiogram and PCI have moderate uneasiness sometimes before the system. [16][17][18] This distinction is because of the obstacles to communication and the mis-understanding of the procedure.…”
Section: Discussionmentioning
confidence: 99%